Learning practice and technology: extending the structurational Practice Lens to educational technology research. Issue 3 (3rd July 2017) - Halperin, Ruth
ABSTRACT: Scholars in the field of educational technology have been calling for robust use of social theory within learning technology research. In view of that, interest has been noted in applying Giddens' structuration theory to the understanding of human interaction with technology in learning settings. However, only few such attempts have been published to date with recent reviews indicating the scarcity of structurational accounts from the educational technology field. Addressing this gap and advancing a critical use of the theory in the field, an attempt is made in this paper to lend coherency to structuration-based research into learning technology. Specifically, a critical consideration of the structurational Practice Lens is offered drawing from its application in a case study that explored technology-mediated learning practices in the institutional context of higher education. Conceptual and analytical aspects are addressed with a view to augment the framework, and to extend its relevance and applicability in educational technology research.